Music as a trigger for craving : exploring the phenomenon and possible music therapy approaches from a client and music therapist perspective - Van de Ree, Maatje (2016)
It is known that craving can be elicited by various triggers, such as visual and auditory cues.Less is known about music as a trigger for craving. Only recently the interest towards this topic has somewhat increased. Two quantitative studies showed that music can increase and evoke craving. Additionally, some music therapists described experiences of their clients with music and craving. Furthermore, few different therapeutic approaches to cope with this phenomenon in music therapy have been proposed. However, the body of research focusing on this topic remains small. Therefore, the purpose of this research is to further explore if music can elicit craving, if so, how music evokes craving and to further explore the music therapy approaches concerning this phenomenon. Due to the exploratory nature of this study, it was decided to conduct qualitative research using semi-structured interviews as data collection method and constructivist grounded theory as method of analysis. The participants were three Dutch music therapists working in the field of addiction care and four clients with substance use disorder. The findings of this study resulted in a conceptualisation of the phenomenon of music as a trigger for craving in which specific music could possibly elicit craving through associations with substance use experiences and negative life-events. The latter resulted in negative emotions, which the clients wanted to suppress through substance use resulting in craving. Whether or not the specific music would elicit craving was influenced by situational factors. Furthermore, several coping strategies were found to deal with music-induced craving. The music therapy approaches appeared to be divided in a direct approach on one hand, focusing directly on the phenomenon by either exposing clients to musical triggers or by the natural occurrence of craving in music therapy. On the other hand, there was an indirect approach, in which music therapists focused on the underlying issues of substance use disorder which seemed to indirectly influence the phenomenon.